CULTURAL ADAPTATION IN A FOREIGN LAND: THE CASE OF NIGERIAN UNDERGRADUATES IN SCOTLAND - Nwafor, Adaobi C; Okonkwo, Emeka T; Ify , O. Eze (International Research Journal of Arts and Communication, 2024)
This study explores the challenges faced by Nigerian undergraduate students in Scotland, UK, focusing on communication culture shock and adaptation strategies. Addressing a gap in literature, it examines the communication techniques used by these students to navigate cultural differences. Anchored in Communication Accommodation Theory (CAT) and Social Identity Theory, the study analyses how students adjust their communication styles and how group identity influences adaptation. Utilising a survey research design, data from 381 Nigerian undergraduate students reveal various adaptation strategies, such as speaking clearly and embracing feedback, to overcome barriers. A survey research design was adopted for this study. The population of this study was made up of Nigerian undergraduate students in Scotland, United Kingdom. According to the Higher Education Statistics Agency (2023), the number of Nigerian undergraduate students in the United Kingdom between the years 2018/2019 through to 2022/2023 is 73,716. Keyton’s formula for sample size determination was used to and the sample size of this study was 381. The snowball sampling was used in different stages. Data were gathered using the copies of the questionnaire which were administered on the respondents virtually. Quantitative data analysis was adopted in this study such as the Statistical Package for the Social Sciences (SPSS), percentages and inferential statistics Chi. The findings revealed that the importance of effective communication in navigating cultural differences, with a consensus on the efficacy of specific techniques. Speaking more slowly and clearly, using less slang and idioms, being more direct and open to feedback and criticism are considered beneficial for effective communication in the UK. The study recommended that Universities in the United Kingdom should foster collaborations with community organizations, Nigerian consular services, and Nigerian cultural associations.